2017
DOI: 10.21767/2473-6457.100019
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the Source of Contamination Opioid into Lead in Forensic Medicine

Abstract: Background: Impurities in narcotics are one of the factors that cause or exacerbate the symptoms of acute and chronic poisoning. Heavy metals as one of the impurities found in the opioids can cause toxicity to consumers. Opioids contamination and its complications are a social health problem in Middle Eastern countries such as Iran. Lead smugglers add more benefits during the drug production process in order to increase their weight.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…Moreover, one of the uncommon causes of lead (Pb) poisoning is Pbadulterated substance abuse, such as opium, marijuana, Iranian crack, ecstasy, and methamphetamine (3). It has been suggested that Pb is added to make the substance heavier (4). It was shown that the highest Pb level was detected in opium samples then heroin and Iranian crack samples were ranked next, respectively.…”
mentioning
confidence: 99%
“…Moreover, one of the uncommon causes of lead (Pb) poisoning is Pbadulterated substance abuse, such as opium, marijuana, Iranian crack, ecstasy, and methamphetamine (3). It has been suggested that Pb is added to make the substance heavier (4). It was shown that the highest Pb level was detected in opium samples then heroin and Iranian crack samples were ranked next, respectively.…”
mentioning
confidence: 99%